Sexual maturation and metabolic profile among adolescents and children of the Health Worker Cohort Study in Mexico Madurez sexual y perfil metabólico de los adolescentes y niños del estudio de cohorte de trabajadores de la salud en México - Jodie G Katon; Yvonne N Flores; Jorge Salmerón (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE:Our objective was to investigate the associations between level and timing of sexual development with metabolic profile in a cohort of Mexican adolescents in central Mexico. MATERIAL AND METHODS:Baseline data from children between the ages of 7 and 17 years (n= 582) who participated in the Health Worker Cohort Study, was used. The study participants included children of workers at the Mexican Institute of Social Security (IMSS) and the National Institute of Public Health, both located in Cuernavaca, in addition to children of workers at the Universidad Autónoma del Estado de México in Toluca who were enrolled between March 2004 and April 2006. Multiple linear regressions with robust estimates of variance, were used adjusting for specific covariates. RESULTS:Both pubertal boys and girls, compared to their pre-pubertal counterparts, had higher body mass index (girls: 4.59 kg/m², p<0.0001; boys: 1.12 kg/m², p= 0.05) and percent body fat (girls: 3.61, p<0.0001; boys: 1.48, p= 0.0001). A significant difference in level of insulin resistance (homeostasis model assessment, HOMA) was detectable among girls (0.92, p<0.0001). CONCLUSIONS:Timing and levels of sexual development were significantly associated with adverse differences in several critical anthropometric and metabolic parameters. OBJETIVO:Investigar las asociaciones entre etapa y momento de inicio del desarrollo sexual y perfil metabólico en una cohorte de adolescentes mexicanos. MATERIAL Y MÉTODOS:Se usó la información basal de los jóvenes entre 7 y 17 años de edad (n= 582), que participaron en el Estudio de cohorte de trabajadores de la salud. Los participantes del estudio fueron los hijos e hijas de los trabajadores del Instituto Mexicano del Seguro Social (IMSS) y del Instituto Nacional de Salud Pública en Cuernavaca, Morelos, así como los hijos e hijas de los trabajadores de la Universidad Autónoma del Estado de México en Toluca. Se realizaron regresiones lineales múltiples con estimadores de varianza robustos, ajustando por covariables específicas. RESULTADOS:Se encontró un índice de masa corporal mayor en los niños y niñas en la etapa de pubertad, comparado con los de pre-pubertad (niñas: 4.59 kg/m², p<0.0001; niños: 1.12 kg/m², p= 0.05) y un mayor porcentaje de grasa corporal (niñas: 3.61, p<0.0001; niños: 1.48, p= 0.0001). Se encontró una diferencia significativa en el indicador de resistencia a la insulina (HOMA, por sus siglas en inglés) en las niñas (0.92, p<0.0001). CONCLUSIONES:La etapa y el momento de inicio del desarrollo sexual se asociaron significativamente con diferencias adversas en varios parámetros metabólicos y antropométricos críticos.